ANALISIS KESALAHAN PENGGUNAAN PARTIKEL DE, NI, DAN O PADA KALIMAT PEMBELAJAR BAHASA JEPANG - novianti, diyah; rosliana, lina; Rini, Elizabeth (Japanese Literature, 2016)
The particles in Japanese called joshi. Joshi has many quantities and variety usesin Japanese. There are many joshi which have similarity in their uses such as de,ni and o. The role of those particles are to show the location where the activityongoing. Many particles has similar sense, it is make the learning process becomedifficult to use those particle. The researcher interest to research the erroranalysis using particles de, ni and o in Japanese learning sentence. Theresearcher used quantitative method. Population on this research was thestudents of Japanese literature of Diponegoro University at 2013 class. Thesample was 64 students and used slovin formula to take the sample. The data wastaken from test and questionnaire. The result of this research were themisapplication of joshi “o” are 63.1%, joshi “ni” are 43.3%, and joshi “de” are50.5%. Then, the average total of analyze misapplication joshi de, ni, and o were52.2%. It showed that the misapplication of joshi de, ni, and o categorize inaverage.